(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: An enlarged neck node is frequently the first clinical manifestation of a neoplastic process in the head and neck region. The earlier the diagnosis is made, the greater the chance of improved survival. A common denominator to all head-neck malignancy is their ability to metastasize. Although metastasis is not a random event, some tumours have the propensity to extensive local invasion without metastasis whereas others metastasize early in their development. Objective: To evaluate the different primary sites metastasizing to cervical lymph nodes. Materials and Methods: A prospective observational study was carried out from July 2007 to March 2009 in the department of Otolaryngology and Head-Neck Surgery, Combined Military Hospital, Dhaka among 60 patients who had metastatic neck nodes with known primary in head-neck region and those with unknown primary were included in this study. Metastatic neck disease involving left supraclavicular or scalene nodes with a possible primary arising within the chest or abdomen were excluded from the study. All cases were advised for Fine Needle Aspiration Cytology (FNAC) of enlarged neck nodes. Tissue samples were taken from primary sites for histopathology. Results: Metastatic neck disease is commonly encountered in Bangladesh. A primary lesion was identified in 53(88.33%) cases however primary sites found undetected in 7(11.67%) cases. Among the primary sites 43(81.13%) cases were seen to arise from squamous lining of upper aero-digestive tract and 10(18.87%) cases were having a nonsquamous origin arising from thyroid gland (13.33%) and parotid gland (3.33%). Among the known primary sites highest incidence of metastatic neck nodes was found with carcinoma- larynx 22(36.66%) and pyriform fossa in 9(15%) cases. Forty seven (78.33%) patients were male and 13(21.67) were female with ratio being 3.6:1 of ages ranging from 20 years to 90 years. Conclusion: Metastatic neck disease in commonly encountered in Bangladesh. Enlarged cervical nodes in an elderly patient should always be considered as metastatic until proved otherwise. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 56-59